A note on the amphibian fauna at Pantai Melawi Bachok, Kelantan - Belabut, D.; Hashim, Rosli; Yong, Hoi Sen; Diah, S.Z.M.; Ahmad, N.; Lim, B.L. (Faculty of Science, University of Malaya, 2010)
Five species of amphibians were found at Melawi, Bachok, Kelantan. Kaloula pulchra, Fejervarya limnocharis and Duttaphrynus melanostictus were the predominant species. Only a single individual of Polypedates leucomystax and an exotic species Hoplobatrachus rugulosus respectively was also found here.